Subglottic stenosis as a presentation of various rheumatic diseases - Bhavya Chintala; Lalit Duggal; Neeraj Jain; Mayank Gupta (Indian Journal of Rheumatology)
The subglottic space at the cricoid level is the narrowest part of the airway. Subglottic stenosis (SGS) is generally benign and may be due to a variety of diseases, but post-intubation injury is the most frequent cause. Other causes are tracheal infections including bacterial tracheitis, tuberculosis, histoplasmosis and diphtheria, and collagen vascular diseases including granulomatosis with polyangiitis, relapsing polychondritis, etc., SGS may be a presenting complaint in rheumatological disorder. In this case series, we shall discuss patients with rheumatic diseases presenting with SGS.